Diagnostic accuracy of 18F-FDG PET/CT for detecting synchronous advanced colorectal neoplasia in patients with gastric cancer. Issue 36 (September 2016) - Choi, Byung Wook; Kim, Hae Won; Won, Kyoung Sook; Song, Bong-Il; Cho, Kwang Bum; Bae, Sung Uk
Abstract : Abstract: Preoperative screening for synchronous colorectal neoplasia (CRN) has been recommended in patients with gastric cancer because patients with gastric cancer are at increased risk for synchronous CRN. The aim of this study was to investigate the diagnostic accuracy of 18 F-fluorodeoxyglucose ( 18 F-FDG) positron emission tomography/computed tomography (PET/CT) for detecting synchronous advanced CRN in patients with gastric cancer. A total of 256 patients who underwent colonoscopy and 18 F-FDG PET/CT for preoperative staging were enrolled in this study. The diagnosis of focal colonic 18 F-FDG uptake on 18 F-FDG PET/CT image was made based on histopathologic results from the colonoscopic biopsy. The 18 F-FDG PET/CT result was considered as true positive for advanced CRN when focal 18 F-FDG uptake matched colorectal carcinoma or adenoma with high-grade dysplasia in the same location on colonoscopy. Synchronous advanced CRN was detected in 21 of the 256 patients (4.7%). Sensitivity, specificity, and accuracy of 18 F-FDG PET/CT were 76.2%, 96.2%, and 94.5%. The size of CRN with a true positive result was significantly larger than that with a false negative result. 18 F-FDG PET/CT demonstrated high diagnostic accuracy for detecting synchronous advanced CRN in patients with gastric cancer. Colonoscopy is recommended as the next diagnostic step for further evaluation of a positive 18 F-FDG PET/CT result in patients with gastric cancer.